Strategi Inovasi untuk Meningkatkan Daya Saing Organisasi di Era Digital - Nur Izsasi Aminah Haryanti; Safinatun Najah; Fidyah Apriliani Fidori; Mu’alimin Mu’alimin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Innovation strategy is a crucial approach to enhancing organizational competitiveness, especially in the digital era marked by rapid technological advancement and increasingly complex competition. This study aims to analyze how innovation strategies can be effectively implemented to improve organizational competitiveness, while also identifying key supporting factors such as digital transformation, innovative culture, external collaboration, leadership, and data-driven decision-making. The research method employed is literature review, drawing from various theoretical frameworks and previous studies. The findings indicate that integrated innovation strategies—including digital process transformation, development of digitally competent human resources, and the establishment of an adaptive organizational culture—significantly contribute to overall organizational performance improvement. The application of advanced technologies such as artificial intelligence and big data also enhances the organization's ability to understand stakeholder needs and design targeted solutions. This study emphasizes that innovation is no longer an option, but a fundamental necessity to ensure organizational sustainability, relevance, and competitive advantage in the digital age.